2009
DOI: 10.1899/08-153.1
|View full text |Cite
|
Sign up to set email alerts
|

Urban streams across the USA: lessons learned from studies in 9 metropolitan areas

Abstract: Studies of the effects of urbanization on stream ecosystems have usually focused on single metropolitan areas. Synthesis of the results of such studies have been useful in developing general conceptual models of the effects of urbanization, but the strength of such generalizations is enhanced by applying consistent study designs and methods to multiple metropolitan areas across large geographic scales. We summarized the results from studies of the effects of urbanization on stream ecosystems in 9 metropolitan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
140
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(154 citation statements)
references
References 69 publications
12
140
1
1
Order By: Relevance
“…Allan (2004) suggested that silty sediments may limit the ability of algal accumulation in urban (Walsh 2004). Urban streams are characterised by a community of tolerant taxa (Helms et al 2009), and these results are consistent with those described elsewhere (Brown et al 2009;Ramı´rez et al 2009). Stepenuck et al (2002 assessed invertebrate communities in response to changes in urbanisation and water quality and a decrease in functional feeding groups (shredders, collectors and predators) generally associated with allochthonous resources.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Allan (2004) suggested that silty sediments may limit the ability of algal accumulation in urban (Walsh 2004). Urban streams are characterised by a community of tolerant taxa (Helms et al 2009), and these results are consistent with those described elsewhere (Brown et al 2009;Ramı´rez et al 2009). Stepenuck et al (2002 assessed invertebrate communities in response to changes in urbanisation and water quality and a decrease in functional feeding groups (shredders, collectors and predators) generally associated with allochthonous resources.…”
Section: Discussionsupporting
confidence: 75%
“…Brown et al 2009;Ramı´rez et al 2009). Banks were heavily incised and substrates were dominated by fine silts, with little retention of organic matter apparent as accumulations of leaf litter or snags (Parkinson pers.…”
Section: Discussionmentioning
confidence: 99%
“…Influence of site factors such as habitat structure on fish assemblages has been investigated extensively (Schlosser, 1982;Harding et al, 1998;Brown et al, 2009). The structure of stream fish assemblages has been related to numerous site variables, such as bottom type and cover (Angermeier & Winston, 1998), and bottom, depth, and current (Gorman & Karr, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, local habitat conditions are directly or indirectly affected by catchment conditions, including land use changes (e.g., Sály et al, 2011;Marzin et al, 2012;Macedo et al, 2014). Local habitat conditions are a fundamental factor for determining the structure and composition of stream biota (Schlosser, 1982;Rosenzweig, 1995;Harding et al, 1998;Brown et al, 2009). For example, fish assemblages are strongly influenced by site channel structure and hydraulic conditions, such as substrate, canopy shading, fish cover, wetted width, depth variation, and slope (Gorman & Karr, 1978;Wang et al, 1998;.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent New Zealand study illustrated how different water quality, macroinvertebrate and fish indicators varied in their responses to land-use stressors (Clapcott et al, 2012). Comparable studies suggest that the assessment of multiple groups of organisms has the potential to provide a more robust evaluation of ecological integrity than the assessment of a single group (Brown et al, 2009;Waite, 2014). Our goal was to combine multiple indicators of stream health into a MMI to provide a more holistic measure of EI than the use of individual indicators.…”
Section: Introductionmentioning
confidence: 99%